Drivers for and Obstacles to Corporate Social Responsibility Practices in Vietnam - A Study in Small and Medium Enterprise Exporters - Le, Thi Thanh Xuan (H. : ĐHQGHN, 2018)
Based on the fact that most factories/manufacturers failed to comply with foreign customers‟ requirements for Corporate Social Responsibility (CSR) practices from first audits, the present study aims to explore Small and Medium Enterprise (SME) exporters‟ understanding of the CSR requirements of foreign clients and motivations and obstacles for them to practice and implement CSR. In order to tackle the research objectives, a qualitative approach is chosen and indepth interviews with owners, HR/CSR managers and production managers are employed to collect data. The research scope is firms/suppliers in hardlines (non-furniture and non-apparel) section. Thematic analysis is used to analyse and categorise data from interviews. The research findings show some crucial points. Firstly, the CSR requirements of clients are not correctly understood. Secondly, there are seven drivers for CSR practices which match with previous studies. Lastly, six out of the ten obstacles to implement CSR are new findings in the present research context. From these findings, some recommendations are proposed to improve CSR practices in SMEs.